Corporate Social Responsibility along the global value chain - Herkenhoff, Philipp,Krautheim, Sebastian,Semrau, Finn Ole,Steglich, Frauke (CESifo, Center for Economic Studies & Ifo Institute, 2021)
Firms are under increasing pressure to meet stakeholders’ demand for Corporate Social Responsibility (CSR) along their global value chains. We study the incentives for and investments in CSR at different stages of the production process. We analyze a model of sequential production with incomplete contracts where CSR by independent suppliers differentiates the final product in the eyes of caring consumers. The model predicts an increasing CSR profile for suppliers along the value chain: from upstream suppliers with low CSR to downstream suppliers with higher CSR. We confirm this prediction using Indian firm-level data. We compute a firm’s value chain position combining product-level information in our data with the World Input-Output Database. We find that more downstream firms have higher CSR expenditures as measured by a combination of staff welfare spending and social community spending.
10419/252015
Keywords: Graue Literatur; corporate social responsibility; global value chains; incomplete contracts; property rights theory; GVC positioning; India; emerging markets